Acesso e mobilidade de afro-descendentes nas organizações - Oliveira, Renato Ladeia de (2006)
The purpose of this thesis is to reveal how Brazilian racism is present in the Brazilian organizations, from national to multinational companies, starting with the perception of afro-descendents at different occupational levels, from specialized workers up to administrative graduated professionals. The development of this project is justified by the lack of specific research within this area, in particular about racism in the daily routines from the Brazilian organizations. The hypothesis that was built is that the national companies would be more racist with afro-descendents than the multinationals or transnationals companies, once these companies have programs to minimize the racism. The reach this objective, testimonials of workers in this situation were analyzed. The research is based on the importance of memory and their possibilities to gather facts whose treatment through this resource seems to be correct. The analysis of ideologies, like the racial democracy and the whiteness, in the studies developed in the last decades, were also important to base the statements analysis. The obtained results enable the identification of other relevant questions related to afro-descendents discrimination in the jobmarket, starting from the first contact when they look for new jobs, at this time, camouflaged and fraudulent mechanisms of racism avoid the entrance of these professionals in the jobmarket. If this phase is passed by, new obstacles are created to difficult the jobmobility